PENGARUH PENDEKATAN CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR SISWA TEMA 7 INDAHNYA KERAGAMAN DI NEGERIKU KELAS IV SDN BADEAN 1 BONDOWOSO - Erika Ayuningtias Darmawan; Chumi Zahroul Fitriyah; Kayan Swastika; Zetti Finali; Dyah Puspita (Universitas Negeri Surabaya, 2023)
This study aims to determine whether there is an effect of Contextual Teaching and Learning approach on student learning outcomes of theme 7 The beauty of diversity in my country, grade IV SDN Badean 1 Bondowoso. This type of research is experimental research. The research design used was a (quasi-experimental design) with a non-equivalent control group pattern. The subjects of this study were fourth grade students of SDN Badean 1 Bondowoso. The data analysis technique used t-test to determine the difference before being given treatment (pre-test) and after being given treatment (post-test). The results of the analysis using the independent samples t-test test obtained the results t_count > t_table which is 3,122 > 2,000, then H0 is rejected and Ha is accepted, which means that there is an effect of Contextual Teaching and Learning approach on student learning outcomes in theme 7 The beauty of diversity in my country, grade IV SDN Badean 1 Bondowoso.